Preparation of Modified Carbon Nanotube Polyvinylidene Fluoride Composite Film and Its Application in Packaging Design - Feng Yuan; Sen Li (Advances in Materials Science and Engineering)
Sustainable design does not emphasize the safety of the ecosystem, but builds a systematic innovation process, taking into account customer needs, environmental benefits, social benefits, and corporate development. This article is based on the preparation of a modified carbon nanotube polyvinylidene fluoride composite film to analyze its application value in packaging design, aiming at analyzing the performance of the modified carbon nanotube and the polyvinylidene fluoride composite film during the preparation process, and applying its various characteristics to the process of packaging design optimization concept. The article is mainly divided into two parts: preparing modified carbon nanotubes and preparing polyvinylidene fluoride composite films. Among them, the photomechanical properties of carbon nanotubes, the relationship between the composition of the composite material and the dielectric properties, the dielectric response and relaxation behavior, the hydrophilicity of the composite membrane, and the membrane separation technology were discussed, and the carbon nanotubes were constructed. Incorporating carbon nanotubes into carbon fiber hybrid materials, and combining carbon nanotubes with polymer materials, works extremely well. The structure model is prepared, the molecular pore size, hydrophilicity, etc. are recorded, and surface modification, chemical modification, blending modification, and other methods are applied to analyze and evaluate the data. The experimental results show that in the application of modified carbon nanotubes and polyvinylidene fluoride composite films and packaging design, the interactive function of toughening modification increases 2.44 points; through enhancement modification, packaging design reduction increases by 2.5 points; and through the compatibilization modification, the functionality of the packaging design has increased by 1.88 points.